2010
DOI: 10.1007/s10295-010-0761-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficient production of lactic acid from sucrose and corncob hydrolysate by a newly isolated Rhizopus oryzae GY18

Abstract: The aim of this study is to investigate production of L-lactic acid from sucrose and corncob hydrolysate by the newly isolated R. oryzae GY18. R. oryzae GY18 was capable of utilizing sucrose as a sole source, producing 97.5 g l(-1) L-lactic acid from 120 g l(-1) sucrose. In addition, the strain was also efficiently able to utilize glucose and/or xylose to produce high yields of L-lactic acid. It was capable of producing up to 115 and 54.2 g l(-1) lactic acid with yields of up to 0.81 g g(-1) glucose and 0.90 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 34 publications
0
15
0
5
Order By: Relevance
“…At the other CaCO 3 concentrations (0, 10, and 30 g/L), determined pHs were 4.4, 5.1, and 6.0, respectively. Optimal CaCO 3 concentration of 20 g/L was lower than those reported in the previous studies [25][26][27]. For example, Wu et al [27] reported that the maximum lactic acid production by R. oryzae was achieved when 50 g/L CaCO 3 were used as neutralizing agent.…”
Section: Effect Of Calcium Carbonate On L-lactic Acid Synthesis and Cmentioning
confidence: 79%
“…At the other CaCO 3 concentrations (0, 10, and 30 g/L), determined pHs were 4.4, 5.1, and 6.0, respectively. Optimal CaCO 3 concentration of 20 g/L was lower than those reported in the previous studies [25][26][27]. For example, Wu et al [27] reported that the maximum lactic acid production by R. oryzae was achieved when 50 g/L CaCO 3 were used as neutralizing agent.…”
Section: Effect Of Calcium Carbonate On L-lactic Acid Synthesis and Cmentioning
confidence: 79%
“…Rhizopus species, such as R. oryzae and R. arrhizus, have amylolytic enzymatic activity, which enables them to convert starch directly to L(+)-lactic acid. Several studies have reported on the use of Rhizopus for lactic acid production (Yin et al 1998;Liu et al 2006;Yu et al 2007;Guo et al 2010;Wu et al 2011;Saito et al 2012). Fig.…”
Section: Bioresourcescommentioning
confidence: 99%
“…However, other production routes, using starchy and lignocellulosic materials as more cost-effective feedstocks, have also been explored (Zhang et al, 2007). In addition to glucose, sucrose is being examined for L-lactic acid production; the yield of 0.81 g/g is however difficult to obtain on a regular basis (Guo et al, 2010). In a recent study concerning the use of starch-containing substrates, a yield of 0.72 g L-lactic acid per gram potato starch was attained, when using Rhizopus in pellet form (Yen & Lee, 2010).…”
Section: Lactic Acidmentioning
confidence: 99%